Two-Q-boson interferometry and generalization of the Wigner function - Padula, Sandra S.; Zhang, Q. H. (AIP Publishing, 2004)
Bose-Einstein correlations of two identically charged Q-bosons are derived considering those particles to be confined in finite volumes. Boundary effects on single Q-boson spectrum are also studied. We illustrate these effects by two examples: a toy model (one-dimensional box) and a confining sphere. We also derive a generalized expression for the Wigner function depending on the deformation parameter Q, which is reduced to its original functional form in the limit Q → 1.